2008
DOI: 10.1017/s1368980007000225
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a diet history questionnaire for use with Costa Rican adults

Abstract: Objective: To validate a diet history questionnaire (DHQ) using a weighed food record (WFR) as the standard method in the estimation of food consumption and nutrient intake in a group of adults. Design: WFR: all foods consumed by subjects during 7 consecutive days were weighed and recorded by nutrition students. Two DHQ interviews were carried out on days 1 (first diet history questionnaire, DHQ1) and 28 (second diet history questionnaire, DHQ2). Setting: Costa Rica. Subjects: Sixty adults: 30 men and 30 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Several studies report higher intakes of energy and nutrients assessed by diet history interviews in comparison with food records [27, 28, 36–40] or 24-h recalls [29]. The relative differences described in these studies are comparable to the presented results.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Several studies report higher intakes of energy and nutrients assessed by diet history interviews in comparison with food records [27, 28, 36–40] or 24-h recalls [29]. The relative differences described in these studies are comparable to the presented results.…”
Section: Discussionsupporting
confidence: 81%
“…As in the present study, Chinnock [27] found the best agreement coefficients between different methods for beverages. Possible reasons for the good agreement of beverages are the small variance of household measures, such as glasses, cups or bottles, and constant day-to-day habits of beverage consumption.…”
Section: Comparison On the Level Of Food Consumptionsupporting
confidence: 82%
See 2 more Smart Citations
“…Three papers in this issue focus on validation testing of dietary intake assessment tools. Marcotte et al (8) assess a calcium checklist for early elementary-school children, Chinnock (9) validates a diet history questionnaire for use with Costa Rican adults and Charlton et al (10) validate a short questionnaire to assess sodium intake. It seems that much of what we do in public health nutrition comes back to assessment and measurement, so these papers will no doubt be of interest.…”
mentioning
confidence: 99%